Gender Diversity and Inclusion: Contemporary and Historical Perspectives - Shabliy, Elena V.; Kurochkin, Dmitry; Ayee, Gloria Y. A.; Wall, Tony (Lexington Books, 2023)
Gender Diversity and Inclusion: Contemporary and Historical Perspectives offers a rigorous analysis of comparative gender-sensitive policy and perspectives regarding gender justice and equity at global, national, and local levels. Presenting and analyzing case studies from countries around the world, including the United States, Northern Ireland, India, Bangladesh, and Iran, the essays in this collection posit that gender equity dialogue and policy advancement are the main key components to progress and perseverance in gender justice—both for positive outcomes and policy making at the global level. In addition, the contributors illustrate that greater gender equity and justice realization influences smart economy development, enhancing progress and improving other positive outcomes, including prospects for intergenerational justice and for the quality of societal policies and institutions.